PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) DENGAN MEDIA BENDA KONKRET DALAM PENINGKATAN PEMBELAJARAN IPA DI KELAS V SDN 2 BUMIAGUNG TAHUN AJARAN 2014/2015 - Winda Mitraningsih, Yuanita (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract : The Use of Cooperative Learning Model Two Stay Two Stray (TSTS) Type by Concret Media in Improving Natural Science Learning at The Fifth Grade Studet of SDN 2 Bumiagung. This research aims to improving natural science learning about simple machines. The subjects were fifth grade students of elementary school totaling 36 students. Colaborative Classroom Action Research was conducted in three cycles. Each cycle there were two meetings that consist of planning, action, observation, and reflection. Data collection techniques used testing, observation and interviews. The validity of data used triangulation techniques and triangulation of data sources. Data analysis applied the analysis of qualitative data and quantitative data. The results showed the use of cooperative models TSTS type by concret media can be improve natural science learning for fifth grade student of elementary school. Keywords: Two Stay Two Stray ,Concret Media, Natural Science Abstrak : Penggunaaan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray dengan Media Benda Konkret dalam Peningkatan Pembelajaran IPA di Kelas V. Penelitian ini bertujuan untuk meningkatkan pembelajaran IPA pada materi pesawat sederhana. Subjek penelitian ini siswa kelas V SDN 2 Bumiagung sejumlah 36 siswa. Penelitian Tindakan Kelas ini dilaksanakan dalam tiga siklus. Setiap siklus terdapat dua pertemuan terdiri dari tahap perencanaan, pelaksanaan tindakan, pengamatan, dan refleksi. Teknik pengumpulan data dengan tes, observasi dan wawancara.Validitas data menggunakan triangulasi data dan sumber. Analisis data dilakukan melalui analisis data kualitatif dan kuantitatif. Hasil penelitian menunjukkan penggunaan model kooperatif tipe TSTS dengan media benda konkret dapat meningkatkan pembelajaran IPA di kelas V SD. Kata Kunci: Two Stay Two Stray, Benda Konkret, IPA